1977
DOI: 10.1159/000251036
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Human Semen in Topical Corticosteroid-Treated and in Methotrexate-Treated Psoriatics

Abstract: Ejaculates were studied from ten men with severe psoriasis treated with topical corticosteroids and from ten similar patients who had received methotrexate therapy from 1 to 9 years. It was not possible to demonstrate any unfavorable effect on the semen quality during the methotrexate therapy. The semen analysis was more frequently found normal (p = 0.04) in the methotrexate treated group, and no specific abnormality was found in spermatozoa of methotrexate-treated patients. Methotrexate therapy to male psoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…The results were unrelated to the clinical type or to the duration of the disease. This agrees with the study carried by Gunther [5] and Grunnet et al [3] on psoriatic males before, during, and in some cases after treatment with methotrexate. These studies also demonstrated no uniform alteration in semen samples.…”
Section: Discussionsupporting
confidence: 93%
“…The results were unrelated to the clinical type or to the duration of the disease. This agrees with the study carried by Gunther [5] and Grunnet et al [3] on psoriatic males before, during, and in some cases after treatment with methotrexate. These studies also demonstrated no uniform alteration in semen samples.…”
Section: Discussionsupporting
confidence: 93%
“…However, a study by Grunnet et al. did not demonstrate reduction in semen quality of psoriasis patients treated with methotrexate compared with semen of psoriasis patients treated with topical corticosteroids, and instead found that semen analysis in the MTX group was more frequently normal . A study by De Luca et al.…”
Section: Resultsmentioning
confidence: 96%
“…To our knowledge, this is the first consistent study evaluating semen quality in psoriatic patients. In 1977, Grunnet et al [23] showed that male fertility was not impaired by methotrexate treatment although they did find a low semen quality at baseline suggesting that this might be due to psoriatic lesions in the genital tract. Moreover, an impaired testicular function, characterized by an inverse correlation between disease activity and normal sperm morphology and motility, has recently been described in 10 patients affected by spondyloarthritis, 5 of whom had psoriatic arthritis [24] .…”
Section: Discussionmentioning
confidence: 99%